2012
DOI: 10.1007/s11657-012-0098-8
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of and risk factors for radiographic vertebral fractures in older Indian women and men: Delhi Vertebral Osteoporosis Study (DeVOS)

Abstract: The prevalence of vertebral fractures among older Indians was comparable to that reported in Caucasian populations. Prevalence of vertebral fractures increased with age in females, but not in males. Overweight individuals were protected against vertebral fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 13 publications
5
32
1
2
Order By: Relevance
“…The greater bone density in Africans may be protective of fractures, given that fracture rates are similar in AI and Caucasian women (37), whereas BA have lower fracture rates compared with other ethnic groups (3). Our study showed that the BA group had greater BMD at all four sites compared with the AI group.…”
Section: Discussionmentioning
confidence: 99%
“…The greater bone density in Africans may be protective of fractures, given that fracture rates are similar in AI and Caucasian women (37), whereas BA have lower fracture rates compared with other ethnic groups (3). Our study showed that the BA group had greater BMD at all four sites compared with the AI group.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that not assessing L 2 to L 5 has resulted in an underestimation because of missing prevalent and/or incident VFs in this lumbar area. However, according to literature, most VFs occur in the mid-thoracic and thoracolumbar area of the spine, (55)(56)(57)(58)(59)(60) which are both visible on chest CT scans.…”
Section: Limitationsmentioning
confidence: 99%
“…The prevalence of radiographic vertebral fractures in older adults in Delhi has been recently reported to be 17.9% (18.8% male and 17.1% female); indicating that vertebral fracture prevalence in India is similar to Western populations [Figure 5]. [26]…”
Section: Fracture Ratesmentioning
confidence: 99%